The Effectiveness of a Menstrual Hygiene Pocketbook in Improving Knowledge and Hygiene Behavior Among Students at SDN 2 Petuk Katimpun - Sari, Uswatun Hasanah Purnama; Ahmad, Farah Fauziyah Radhiyatulqalbi; Rahmawati, Laila; Siskaevia, Siskaevia (Biomedical Journal of Indonesia, 2025)
Introduction. Menstruation is a natural biological phenomenon experienced by every woman. However, limited knowledge and misconceptions about menstruation can affect reproductive health. This study aims to assess the effectiveness of the Menstrual Hygiene Pocketbook in improving the knowledge and menstrual hygiene behavior of female students in grades 4, 5, and 6 at SDN 2 Petuk Katimpun. Methods. The research method used a quantitative method with a quasi-experiment design; the approach used in this study was a pre-test and post-test design without a control group.  Results. The results show that the average knowledge score of the students increased from 10.09 in the pre-test to 14.53 in the post-test. Students' behavior also showed a significant improvement, with the average pre-test score increasing from 9.59 to 13.26 after receiving education using the pocketbook. Conclusion. The Menstrual Hygiene Pocketbook proves to be an effective tool for enhancing awareness and menstrual hygiene practices among adolescent girls. However, without a control group, conclusions about causality should be drawn with caution, and external factors such as information from parents or the media may influence the study's results.